SEKOLAH DAN MASYARAKAT BERBASIS MULTIKULTURAL - Tri Wahyudi Ramdhan (Edupedia : Jurnal Studi Pendidikan dan Pedagogi Islam, 2019)
This study is a Library Research written based on the results of studies of various library materials, both in the form of books, journals, articles and so on related to schools and communities that are collided with multicultural terms. In line with the method, the data collection techniques used in this study are documentary techniques, in the sense that data is collected through documents as referred to as library material. The data collected in this study is then analyzed using content analysis. The results of the discussion are that multicultural-based schools and communities are formal educational institutions and community environments that uphold and recognize the existence of plurality of identities in the community and willing to accept all forms of diversity